Morpho‐functional analyses reveal that changes in the chemical structure of a marine bisindole alkaloid alter the cytotoxic effect of its derivatives. Issue 7 (3rd March 2022) - Burattini, Sabrina; Battistelli, Michela; Verboni, Michele; Falcieri, Elisabetta; Faenza, Irene; Lucarini, Simone; Salucci, Sara
Abstract: 2, 2‐bis(6‐bromo‐1 H ‐indol‐3‐yl) ethanamine, a marine bisindole alkaloid, showed anticancer property in several tumor cell lines thanks to the presence of a 3, 3′‐diindolylmethane scaffold. Here, the modifications in its chemical structure into alkaloid‐like derivatives, have been evaluated, to investigate changes in its biological activities. Three derivatives have been considered and their potential apoptotic action has been evaluated through morpho‐functional analyses in a human cancer cell line. Apoptosis appears strongly decreased in the derivatives without the bromine atoms (1 ) and in those where the bromine atoms have been substituted with fluorine atoms (2 ). On the contrary, the methylation of indole NH (3 ) does not alter the alkaloid apoptotic activity that occurs through mitochondria involvement supported by cardiolipin peroxidation and dysfunctional mitochondria presence. This manuscript highlights the alkaloid derivative cytotoxic effect, which is strictly correlated to the presence of N‐methylated bisindole alkaloid and bromine atoms, conditions which assure to maintain the pro‐apoptotic activity. Since molecular therapies, by targeting mitochondria pathways, have shown positive outcomes against several cancer cells, the alkaloid with bisindole methylated scaffold and the two bromine atoms can be considered a promising candidate to develop new derivatives with strong anticancer property. Research Highlights: 2, 2‐bis(6‐bromo‐1 H ‐indol‐3‐yl) ethanamine is an alkaloid known for its anticancer properties. Morpho‐functional analyses evaluated cytotoxicity of its synthetic derivatives in tumor cells. Anticancer properties depend on the presence of bisindole scaffold and the two bromine units. Abstract : The marine alkaloid BrDIMEA and some natural antitumoral agents sharing the 3, 3′‐diindolylmethane (DIM) scaffold.